The Understanding of Humor in Turkish Comedy Films: A Reading on Selected films in the 1970s and the 2010s - Çevik, Yasin Alp (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Fundamentally, all societies are constantly in a process of change and development. Social events such as technological, financial, martial, or political are all effective components to assist the process of change of societies. While many social events are occurring in society, cinema would be affected by those happenings in manydimensional manners as well. The ideology of some specific times, directly or indirectly, are taking their place in our lives, and films being an instrument to display and represent the ideologies of that times. Therefore, this study targeted to investigate past and present traces of Turkish comedy films from the Yeşilçam era to the new Turkish cinema period to collect and bridge data to nowadays to be able to understand and compare the alterations in sense of humor. To achieve this aim, three theories of humor (superiority, incongruity, and relief) have been used in the study to deconstruct the humorous moments in selected Turkish comedy films. The selected films ‘‘Tosun Paşa (1976), Şaban Oğlu Şaban (1977), Kibar Feyzo (1978), Recep İvedik (2015), Düğün Dernek 2: Sünnet (2017), and Arif v 216 (2018)’’ have been read with the methodology of textual analysis to understand and highlight key points of humorous moments. To elaborate and understand the structure of humor three theories of humor are applied to the study. Additionally, Ferdinand de Saussure’s dyadic model and Stuart Hall’s theory of representation took place in the study. To sum up, the final analysis shows that there are some differences in sense of humor. The first difference is criticism of power relations in the films are disappeared in new Turkish cinema period, and the second difference is the conversational and behavioral patterns of the characters changed to establish humor.

ÖZ: Özünde tüm toplumlar sürekli bir değişim ve evrim eylemi içindedir. Teknolojik, finansal, askeri veya politik gibi sosyal olayların tümü toplumların değişim sürecine etki eden ve yardımcı olan etkili bileşenlerdir. Toplumda pek çok sosyal olay yaşanırken sinema da bu olaylardan çok boyutlu olarak etkilenmektedir. Belirli zamanların ideolojisi doğrudan ya da dolaylı olarak hayatımızda yerini almakta ve filmler o zamanın ideolojilerini sergileme ve temsil etme aracı olarak işlev görmektedir. Bu nedenle, bu çalışma, Türk komedi filmlerinin Yeşilçam dönemi ve yeni Türk sineması döneminden geçmiş ve günümüzdeki izlerini inceleyerek, mizah anlayışındaki değişimleri anlayabilmek ve karşılaştırabilmek için film okumaları yaparak veri toplamak ve günümüze köprüler kurmayı hedeflemiştir. Bu amaca ulaşmak için seçilen Türk komedi filmleri Yeşilçam döneminden “Tosun Paşa (1976), Şaban Oğlu Şaban (1977), Kibar Feyzo (1978) ile yeni dönem Türk komedi filmlerini temsilen Recep İvedik (2015), Düğün Dernek 2: Sünnet (2017), ve Arif v 216 (2018) filmleri seçilmiştir. Mizahi anların kilit noktalarını anlamak ve vurgulamak için filmler metin analizi metodolojisi ile okunmuştur. Mizahın yapısını detaylandırmak ve anlamak için çalışmaya üç mizah teorisi uygulanmıştır. Bu teoriler sırasıyla üstünlük, uyuşmazlık ve rahatlama teorileridir. Ayrıca Ferdinand de Saussure'un ikili modeli ve Stuart Hall'ın temsil kuramı da çalışmada yer almıştır. Son olarak, mevcut analizler neticesinde mizah anlayışında bazı farklılıkların olduğu gözlenmektedir. Birinci fark, filmlerdeki iktidar (güç) ilişkilerinin eleştirisi yeni Türk sineması döneminde ortadan kalkmıştır, ikinci fark ise karakterlerin mizahı tesis edecek konuşma ve davranış kalıplarıdır.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2021. Supervisor: Asst. Prof. Dr. Yetin Arslan
Keywords: Thesis Tez